A paradigm for the contextual safety assessment of agricultural microbes: a closer look at Klebsiella variicola - Marian, Christina; Sanjar, Fatemeh; Maxwell, Carl; Sabitu, Folashade; Hubbard, Natalie; Ratib, Nicole; Vassilev, Nikolay; Sansinenea, Estibaliz (Frontiers in Industrial Microbiology, 2024)
Adopting a risk assessment paradigm that is contextualized and strain-specific will be critical to enabling the continued development and safe use of microbes, particularly bacteria, in numerous industries and applications. An overly simplistic approach of labeling bacterial species as either harmful or beneficial is ill-suited for the complexities of their interactions with hosts and other microbes, where the lines between friend, foe, and innocent bystander are often unclear. Many such nuanced relationships have been described in human microbiome studies, illustrating the inherent challenges of defining bacterial safety. Any effective risk assessment framework must take into account bacterial niche and environment, fitness, host health, route and extent of exposure, and strain characterization. Klebsiella variicola, a diazotrophic soil bacterium isolated around the world, has been the subject of increasing interest on both environmental and clinical fronts, and has been used commercially as a biofertilizer on millions of farm acres. Here we review its population structure, relevance in clinical and environmental settings, and use as a biofertilizer in light of the risk assessment framework described.